Sedation methods for transthoracic echocardiography in children with Trisomy 21—a retrospective study. Issue 5 (8th February 2017) - Miller, Jeff; Ding, Lili; Spaeth, James; Lam, Jennifer; Paquin, Joanna; Lin, Erica; Divanovic, Allison; Li, Bi Lian; Baskar, Shankar; Loepke, Andreas W.
Summary: Background: Many children with Trisomy 21 have neurologic or behavioral problems that make it difficult for them to remain still during noninvasive imaging studies, such as transthoracic echocardiograms (TTEcho). Recently, intranasal dexmedetomidine sedation has been introduced for this purpose. However, dexmedetomidine has been associated with bradycardia. Children with Trisomy 21 have been reported to have a higher risk of bradycardia and airway obstruction with sedation or anesthesia compared to children without Trisomy 21. Objective: Our aim was to quantify the incidence of age‐defined bradycardia and other adverse effects in patients with Trisomy 21 under sedation for TTEcho using a variety of sedation and anesthesia techniques available and utilized at our institution in this challenging patient population, including intranasal dexmedetomidine, oral pentobarbital, general anesthesia with propofol, and general anesthesia with sevoflurane. Our primary hypothesis was that intranasal dexmedetomidine sedation would result in a significantly higher risk of bradycardia in patients with Trisomy 21, compared with other sedative or anesthetic regimens. Methods: This is a retrospective, observational study of 147 consecutive patients with Trisomy 21 who were sedated or anesthetized for transthoracic echocardiography. Efficacy of sedation was defined as no need for rescue sedation or conversion to an alternate technique. Lowest and highest heart rate, systolic blood pressure, oxygen saturation, and PR interval from formal electrocardiograms were extracted from the electronic medical record. These data were compared to age‐defined normal values to determine adverse events. Results: Four methods of sedation or anesthesia were utilized to perform sedated transthoracic echocardiography: general anesthesia with sevoflurane by mask, general anesthesia with sevoflurane induction followed by intravenous propofol maintenance, oral pentobarbital, and intranasal dexmedetomidine. Intranasal dexmedetomidine 2.5 mcg·kg −1 was an effective sedative as a single dose for TTEcho in 37 of 41 (90%) cases. Oral pentobarbital 5 mg·kg −1 as a single dose for young children with Trisomy 21 was effective in 55 of 75 (73%) cases. Intranasal dexmedetomidine sedation was not associated with a significantly higher risk of bradycardia in patients with Trisomy 21, compared with other sedative or anesthetic regimens, when compared to oral pentobarbital for patients under 2 years of age and general anesthesia for children 3 years and older. The two general anesthesia groups showed lowest heart rates of 66.9 ± 15.9 min −1 for sevoflurane and 69.0 ± 11.5 min −1 for sevoflurane–propofol. Hypotension was present in all groups ranging between an incidence of 56% in the sevoflurane group to 11% in the oral pentobarbital group. Oxygen saturation and clinically significant desaturation occurred in 14% of the oral pentobarbital group. Conclusion: Intranasal dexmedetomidine sedation was not associated with a significantly higher risk of bradycardia in patients with Trisomy 21, compared with other sedative or anesthetic regimens. Abstract :